Why business matters to God (and what still needs to be fixed) - Van Duzer, Jeffrey B. (Downers Grove, Ill. : IVP Academic, 2010)
Jeff Van Duzer presents a profoundly Christian approach that integrates biblical studies with the disciplines of business and economics. Looking beyond the place of ethical principles and the character of the individual, Van Duzer displays a vision of business that contributes to the very purposes of God. --From publisher description.
In the beginning -- Broken -- In the end -- Putting it back together -- Postures of engagement : first excursus -- A thought about institutions : second excursus -- How then should we do business? -- Making it real : a few final questions.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Business -- Religious aspects -- Christianity; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books